2014
DOI: 10.1007/s00787-014-0634-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term course of ADHD symptoms from childhood to early adulthood in a community sample

Abstract: Comparatively little information is available from population-based studies on subgroup trajectories of attention-deficit/hyperactivity disorder (ADHD) core symptoms of inattention and hyperactivity-impulsivity (particularly as defined by DSM-IV and ICD-10). Recent report of a subgroup with high and increasing inattention symptoms across development requires replication. To identify the different trajectory subgroups for inattention, hyperactivity-impulsivity and total symptoms of ADHD in children and adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 30 publications
13
82
1
1
Order By: Relevance
“…Five classes is a larger number than those generally identified for either inattention or hyperactivity/impulsivity in previous studies of ADHD developmental trajectories [e.g. 23,44,51,52]. Previous studies have, however, only included symptoms as reported by a single informant in their models and could, therefore, not identify distinctions between individuals with different patterns of expression across school and home contexts.…”
Section: Discussionmentioning
confidence: 80%
“…Five classes is a larger number than those generally identified for either inattention or hyperactivity/impulsivity in previous studies of ADHD developmental trajectories [e.g. 23,44,51,52]. Previous studies have, however, only included symptoms as reported by a single informant in their models and could, therefore, not identify distinctions between individuals with different patterns of expression across school and home contexts.…”
Section: Discussionmentioning
confidence: 80%
“…Previous ADHD studies have reported a general decline in hyperactivity-impulsivity symptoms severity across development [49,50], whilst for inattentive symptoms the findings are inconclusive. A reduction [51], stability [48] and increase in attention [49] have all been reported. There are few longitudinal studies for DCD, with many methodological differences among these.…”
Section: Developmental Coursementioning
confidence: 94%
“…The developmental course appears to be variable but stable for both disorders [1,40,48]. ADHD symptomatology and motor impairment may vary both in severity and nature, and for both disorders the manifestation of symptoms may differ according to the age at which the diagnosis is considered.…”
Section: Developmental Coursementioning
confidence: 99%
“…Studies indicate that the hyperactive/ impulsive cluster of symptoms tends to wane with age relative to the more enduring inattentive cluster. 8,9,18,19 It has also been suggested that expression of hyperactivity in adults may become internalized as restlessness or inner tension, which may be misinterpreted as anxiety. 9,12 In addition, hyperactive/ impulsive symptoms may become less apparent due to a changing environment with different behavioral constraints.…”
Section: Clinical Symptoms and Neuropsychological Deficitsmentioning
confidence: 97%